Family violence against gay and lesbian adolescents and young people: a qualitative study - Iara Falleiros Braga; Wanderlei Abadio de Oliveira; Jorge Luiz da Silva; Flávia Carvalho Malta de Mello; Marta Angélica Iossi Silva
ABSTRACT Objective: To analyze the experiences of gay and lesbian adolescents and young people in the process of revealing sexual orientation to their families. Method: A qualitative study carried out in a city in the state of São Paulo. Twelve gay and lesbian adolescents and youngsters participated. For the data collection, the semi-structured interview was used and data analysis was performed using the method of interpretation of the senses. Results: The family reactions in the process of "coming out of the closet" of the participants were violent, with persecution and even expulsion from home, in addition to the repression of expressions of homoerotic experiences, which impacted on their health and quality of life. Final considerations: The family is an essential component of the support network, but also a space that can generate and reproduce forms of violence in the name of heteronormativity. Health services should develop care practices and care for the family and adolescent and homosexual youth victim of violence.